PENGARUH MEDIA LOOSE PART BIJI JAGUNG BERWARNA DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA 4-5 TAHUN - Sumarni, Ani; Yustika Rini, Ratu; Sari, Novita; Nur, Maulida; Sina, Ibnu (Education Journal : Journal Educational Research and Development, 2026)
Creativity is a crucial aspect of early childhood development related to imaginative, exploratory, and original thinking abilities. This study aims to examine the effect of using colored corn seed loose parts media on creativity development in children aged 4-5 years. Loose parts media were chosen for their open-ended nature, accessibility, and strong visual and sensory appeal. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group model. The sample consisted of 20 children divided into experimental (n=10) and control (n=10) groups. Data were collected through observation using a creativity assessment sheet based on indicators of fluency, flexibility, and originality. Statistical analysis using t-test showed a significant difference between the experimental and control groups, with t-value of 8.6048 and p = 0.000 (p < 0.05). The average gain score of the experimental group reached 27.7, while the control group only 18.2. These findings indicate that the use of colored corn seed loose parts has a significant positive impact on enhancing children's creativity. This study contributes to the development of environmentally friendly educational media based on local materials that support contextual learning in early childhood education settings.